Amicus Curiae at the Crossroads of Justice: Shaping Fair Court Decisions - Sahuri Lasmadi; Angga Aldilla Gusman; Moh Hasyim Asy'ari; Ammar Zul Haidar; Mutia Carolina Fransica (Unnes Law Journal, 2025)
Judges play an important role in the implementation of law enforcement, as they are tasked with making decisions that reflect the principles of justice. In their decision-making process, judges must consider and align with the values embedded in the community, as the law exists to serve humanity, not the other way around. The concept of Amicus Curiae (friends of the court) refers to input provided by individuals or organizations that are not directly involved in a case but have a vested interest in its outcome. This research explores the significance of Amicus Curiae in the Indonesian legal system, specifically examining its potential to optimize legal justice. It also investigates how judges incorporate Amicus Curiae submissions into their decision-making process to ensure fair and just rulings. The research adopts a normative juridical approach, utilizing legal, case, comparative, and conceptual analyses. The findings reveal that Amicus Curiae can play a crucial role in enhancing the judicial process in Indonesia by providing valuable perspectives on facts and legal issues pertinent to the case. While it does not interfere with the core issues being examined by the judges, Amicus Curiae contributes to the overall understanding of the case, thereby facilitating more informed, equitable decisions. The presence of Amicus Curiae in legal proceedings ultimately supports the realization of justice by shedding light on important legal and factual matters.